Pengaruh Perencanaan Diet Diabetes Mellitus dengan Model Self Care terhadap Diet Self Care Behavior dan Kolesterol Total pada Klien dengan Diabetes Mellitus Tipe 2 di Wilayah Kerja Puskesmas Rambipuji Kabupaten Jember (The Influence of Diet Planning Diabe - Gigih Permana Kusuma Putra; Rondhianto Rondhianto; Dodi Wijaya (Pustaka Kesehatan, 2015)
Type 2 diabetes is a chronic disease caused by insulin resistance in the body. Diabetes Diet for a client with diabetes mellitus type 2 is used to look at dietary self-care behaviors and control the total cholesterol is a risk factor for cardiovascular disease. The purpose of the study was to analyze the effect of the diet plan for diabetes self-care behaviors and total cholesterol diets client type 2 diabetes mellitus in Puskesmas Rambipuji Jember. The study design was quasi-experimental with equivalent control group pretest posttest design. The treatment group was given treatment (application of diet diabetes mellitus), in the untreated control group. The results showed significant differences in dietary self-care behaviors between the treatment group and the control group, but for total cholesterol was no significant difference between the treatment and control groups. The results of the independent t-test on the variable dietary self-care behaviors scored 2,555 t (p = 0.016), while the value of t -0997 total cholesterol (p = 0328). There is influence of a diet plan to diet diabetes with self care model for self-care behaviors and total cholesterol in type 2 diabetes mellitus client.   Keywords: diabetes mellitus type 2, diabetes diet plan, dietary self-care behavior, total cholesterol